Inspiracje filozoficzne i religijne dla zakazu piętnowania twarzy skazańców. Ze studiów nad konstantyńską humanitas - Zalewski, Bartosz (Czasopismo Prawno-Historyczne, 2018)
The aim of this paper is to analyze the constitution by Constantine the Great which prohibited the branding of faces of the condemned to the gladiatorial games (Latin damnatio in ludum) or to the mines (Latin damnatio in metallum). Recognized as the leading exemplar of humanitarianism and an outwardly simple legal act, it inspires one to ask questions about the intellectual and religious inspirations of the lawmaker. This allows one to consider the shape of the humanitas notion during the reign of Constantine the Great.